2011
DOI: 10.3892/ijmm.2011.804
|View full text |Cite
|
Sign up to set email alerts
|

Association of a matrix metallopeptidase 1 gene polymorphism with long-term outcome of thoracic aortic aneurysm

Abstract: Abstract. Although genetic variants are thought to contribute to the development of thoracic aortic aneurysm including dissection (TAA), it remains unclear whether gene polymorphisms are associated with the long-term outcome of TAA. The purpose of the present study was to identify genetic variants associated with the long-term outcome of medically treated patients with TAA. A total of 103 medically-treated patients with TAA (13 aneurysms and 90 dissections) were retrospectively studied for their outcomes (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Evaluation of genotype distributions by the Chi-square test and subsequent multivariable logistic regression analysis with adjustment for covariates revealed that the −340A → G polymorphism (rs514921) of MMP-1 gene was significantly (P = 0.0288) associated with the outcome of TAA, with the minor G allele being related to a favorable outcome [30].…”
Section: Mmp-pathwaysmentioning
confidence: 99%
“…Evaluation of genotype distributions by the Chi-square test and subsequent multivariable logistic regression analysis with adjustment for covariates revealed that the −340A → G polymorphism (rs514921) of MMP-1 gene was significantly (P = 0.0288) associated with the outcome of TAA, with the minor G allele being related to a favorable outcome [30].…”
Section: Mmp-pathwaysmentioning
confidence: 99%
“…In a smaller study, it was suggested that patients with STAAD were five times more likely to have the G-allele of the MMP9 -8202A/G polymorphism compared with control subjects 53. Other studies have demonstrated associations with SNPs on 9p21 (near CDKN2B-AS1 ) and in MMP1 gene 54 55. Matrix metalloproteinases are enzymes involved in the breakdown of extracellular matrix.…”
Section: Copy Number Variation and Single-nucleotide Polymorphisms Unmentioning
confidence: 99%
“…[1,15,16] Previous studies have shown an association between ACE gene polymorphism and matrix metallopeptidase-1 gene polymorphism and AD. [12,13] To our knowledge, this is the first study investigating the relationship between AD and eNOS 4a/b polymorphism.…”
Section: Discussionmentioning
confidence: 94%
“…[6][7][8][9][10][11] Additionally, the eNOS gene polymorphism has been shown to be associated with HT. [12,13] In AD, formation of intimal tear and dissection represents the end point of chronic atherosclerotic and inflammatory changes in the aortic wall. It is possible that impaired metabolism of NO secondary to genetic predisposition may influence the aortic wall.…”
mentioning
confidence: 99%